2004
DOI: 10.1089/1093507041253235
|View full text |Cite
|
Sign up to set email alerts
|

Improved Asthma Outcomes Using a Coordinated Care Approach in a Large Medical Group

Abstract: The objective of this study was to review the development of a multidisciplinary asthma disease management program in a large medical group practice in an urban area, and evaluate the impact of the program on processes of care and health care utilization for adults and children with asthma. The disease management intervention included the development of a patient registry, a systematic approach to assessment of asthma control using the Asthma Therapy Assessment Questionnaire (ATAQ), case management, and physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 16 publications
0
41
0
1
Order By: Relevance
“…79,80,89 Only 1 of 4 studies, a pre-post study, reported a significant reduction in ED visits: a 41% reduction in ED visits and 54% reduction in hospitalizations (P , .001 for both). 90 The other pre-post study reported a 4% reduction in hospitalizations (no P value reported). 80 The 2 RCTs reported 1% (P .…”
Section: Organizational Changementioning
confidence: 91%
See 3 more Smart Citations
“…79,80,89 Only 1 of 4 studies, a pre-post study, reported a significant reduction in ED visits: a 41% reduction in ED visits and 54% reduction in hospitalizations (P , .001 for both). 90 The other pre-post study reported a 4% reduction in hospitalizations (no P value reported). 80 The 2 RCTs reported 1% (P .…”
Section: Organizational Changementioning
confidence: 91%
“…89,90 A pre-post study (instituting a registry to track asthma patients and an asthma case manager) reported a 10% increase in patient education (P , .001) and a 14% increase in asthma action plan dispensations (P , .001). 90 In the RCT (a restructured clinical protocol for how asthma patients are cared for during ambulatory care encounters; "3+ visit plan"), there was a 10% increase in the provision of asthma education (P = .01). 89 SOE: low.…”
Section: Organizational Changementioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Studies of approaches to improving practitioners' adherence to the guidelines have found that a variety of multidimensional approaches to clinician education are somewhat effective in changing physician behavior and improving health outcomes. 4,[7][8][9][10][11] However, a randomized, controlled trial of a continuous quality improvement intervention did not significantly affect processes or outcomes of care for children with asthma. 12 What generally emerges from the literature is that to be effective, interventions must be tailored to the environment and culture in which they are implemented.…”
Section: Introductionmentioning
confidence: 99%